Whole-body MR imaging including angiography: predicting recurrent events in diabetics - Bertheau, Robert; Kauczor, Hans-Ulrich; Schönberg, Stefan; Weckbach, Sabine; Schlett, Christopher L. (European radiology, 2016)
Objectives: Whether whole-body MRI can predict occurrence of recurrent events in patients with diabetes mellitus. Methods: Whole-body MRI was prospectively applied to 61 diabetics and assessed for arteriosclerosis and ischemic cerebral/myocardial changes. Occurrence of cardiocerebral events and diabetic comorbidites was determined. Patients were stratified whether no, a single or recurrent events arose. As a secondary endpoint, events were stratified into organ system-specific groups. Results: During a median follow-up of 70 months, 26 diabetics developed a total of 39 events; 18 (30 %) developed one, 8 (13 %) recurrent events. Between diabetics with no, a single and recurrent events, a stepwise higher burden was observed for presence of left ventricular (LV) hypo-/akinesia (3/28/75 %, p < 0.0001), myocardial delayed-contrast-enhancement (17/33/63 %, p = 0.001), carotid artery stenosis (11/17/63 %, p = 0.005), peripheral artery stenosis (26/56/88 %, p = 0.0006) and vessel score (1.00/1.30/1.76, p < 0.0001). After adjusting for clinical characteristics, LV hypo-/akinesia (hazard rate ratio = 6.57, p < 0.0001) and vessel score (hazard rate ratio = 12.29, p < 0.0001) remained independently associated. Assessing organ system risk, cardiac and cerebral MR findings predicted more strongly events in their respective organ system. Vessel-score predicted both cardiac and cerebral, but not non-cardiocerebral, events. Conclusion: Whole-body MR findings predict occurrence of recurrent events in diabetics independent of clinical characteristics, and may concurrently provide organ system-specific risk.
Gesehen am 29.04.2019
Published online: 25 August 2015